1973
DOI: 10.3758/bf03198110
|View full text |Cite
|
Sign up to set email alerts
|

I recognize your face but I can’t remember your name: Further evidence on the tip-of-the-tongue phenomenon

Abstract: Fifty faces of "famous" persons were used as stimuli to precipitate the tip-of-the-tongue (TOT) experience. Results showed that Ss in TOT states searched for target's name by locating first his profession, where he was most often seen, and how recently. Ss also had accurate knowledge of the initial letters of target names, initial letters of similar sounding names, and numbers of syllables in target names. It was concluded that TOT states for to-be-remembered names are retrieved from semantic and episodic memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
71
0
2

Year Published

1974
1974
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 3 publications
9
71
0
2
Order By: Relevance
“…Thus, these findings extend the results of previous studies that have elicited TOT states with either multisyllabicwords or proper nouns (see also Burke et al, 1991;Riefer, Keveri, & Kramer, 1995;S. M. Smith, Brown, & Balfour, 1991;Yarmey, 1973), and suggests the TOT state is most likely due to failures of a general lexical retrieval process rather than the failure of some special process used to retrieve unique or unusual words. Recall the relationships between word length and word frequency (Zipf, 1935), word length and neighborhood density (Bard & Shillcock, 1993;Pisoni et al, 1985), and word frequency and neighborhood density (Landauer & Streeter, 1973) for evidence that long, multisyllabic words are indeed unique and unusual.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, these findings extend the results of previous studies that have elicited TOT states with either multisyllabicwords or proper nouns (see also Burke et al, 1991;Riefer, Keveri, & Kramer, 1995;S. M. Smith, Brown, & Balfour, 1991;Yarmey, 1973), and suggests the TOT state is most likely due to failures of a general lexical retrieval process rather than the failure of some special process used to retrieve unique or unusual words. Recall the relationships between word length and word frequency (Zipf, 1935), word length and neighborhood density (Bard & Shillcock, 1993;Pisoni et al, 1985), and word frequency and neighborhood density (Landauer & Streeter, 1973) for evidence that long, multisyllabic words are indeed unique and unusual.…”
Section: Discussionsupporting
confidence: 76%
“…Brown and McNeill (1966) and Koriat and Lieblich (1974) showed that during a TOT state, participants often had access to information about the number of syllables and the identity of the first and last letters of common nouns that they were trying to recall. Yarmey (1973) reported similar results for names of famous people; participants often knew the first letter and number of syllables when in a TOT state for a person's name. The present study investigated TOT states when participants were attempting to name famous people whose names contained two words (e.g., Liz Hurley and Gwyneth Paltrow) or three words (e.g., Jamie Lee Curtis and Olivia Newton John).…”
supporting
confidence: 63%
“…Instead, because information was probably available about the number of syllables in a person's name (Yarmey, 1973), the participants may have made their estimation of the number of words on the basis of the syllable length of the person's name. However, there was no significant correlation between the number of syllables in a name and the number of times that a name was considered to comprise three words by the participants who were in a TOT state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the tip-of the-tongue phenomenon for example cf. Brown and McNeill (1966) and Yarmey (1973)' When a word is on the tip of the tongue, speakers can often specify how many syllables the word contains and which syllable receives primary stress-all without knowing what phonemes make up the syllables. The generic specification of words, as seen in the tip-of-the-tongue phenomenon, favors a model with the same general characteristics as the Recoding Theory.…”
Section: Discussionmentioning
confidence: 99%